Penerapan Akuntansi Aset tetap Menurut PSAK No.16 Pada Foodpoint Mall. Lembuswana Samarinda - Adisthy Shabrina Nurqamarani, Suriani Elfreda Aplonia Lau 2 (EKONOMIA, 2020)
This study aims to determine the recognition, measurement and presentation of fixed assets in the financial statements conducted by Foodpoint Lembuswana Mall based on the Statement of Financial Accounting Standards (PSAK) No.16 The analytical tool used in this study is a comparative descriptive method, which is a method that compares accounting treatments that include recognition, measurement and presentation of fixed assets in the financial statements according to Statement of Financial Accounting Standards (PSAK) No.16 versus financial statement of Â Foodpoint Mall Lembusana and also the Champion method to calculate the value of the checklist in determining the suitability criteria.Based from the results calculated by Dean J. Champion shows the he recognition of fixed assets 50% (unfit), the measurement of fixed assets 0% (not suitable), Presentation of fixed assets in the financial statements 0% (not suitable).The conclusion of this research is the recognition of fixed assets in Foodpoint Mall inadequate according to PSAK No. 16 so that the hypothesis is accepted, the measurement of fixed assets in Foodpoint Mall is inadequate according to PSAK No. 16 so that the hypothesis is accepted, the presentation of fixed assets in the financial statements in the Foodpoint Mall in Lembuswana not appropriate based on PSAK No. 16 so that the hypothesis is accepted